A new control approach to variable speed PM wind generator for enhancing dynamic stability of wind farm - Rosyadi, M.; Muyeen, S.M.; Takahashi, R.; Tamura, J. (Praise Worthy Prize, 2012)
In this paper a new control scheme for variable speed permanent magnet wind generator connected to grid through LC filter is proposed in order to enhance stability of wind farms including fixed speed induction generators. Design and control approaches of two level back to back converters are developed in order for both active and reactive powers delivered to a power grid system to be controlled effectively. The stability performances of the controller system such as characteristic of dynamic response and good margin are also investigated based on the bode diagram. To evaluate the controller system capabilities, simulation analyses for both transient and steady state conditions are performed on a model system composed of two wind farms connected to an infinite bus. The simulations have been performed using PSCAD/EMTDC. The results show that the proposed controller is highly effective to augment voltage stability of the wind farm.